2021
DOI: 10.1111/1753-6405.13164
|View full text |Cite
|
Sign up to set email alerts
|

Does community cultural connectedness reduce the influence of area disadvantage on Aboriginal & Torres Strait Islander young peoples’ suicide?

Abstract: ast and present colonisation in Australia has resulted in injustice against First Peoples through forced removal of communities from traditional homelands and children from their families, as well as genocide, dispossession, subjugation and discrimination. [1][2][3] Discriminatory legislation, paradoxically titled 'Protection Acts' , provided state governments, or 'Chief Protectors', the authority to remove children without evidence of neglect, take property and deny access to lands, displace people, control w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The results in the present study support the relationships described in the FNMWCF model-specifically, that belonging fostered through culture is a significant predictor of engagement in land-based activities. This finding supports existing models that describe how increased engagement in cultural practices and identities among Indigenous communities is protective against adverse physical and mental health outcomes, including racial discrimination, colonialism, and historical trauma [33,38,39,49]. For example, cultural resilience has been significantly associated with mental, physical, emotional, and spiritual wellbeing, including self-reported physical health [49].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results in the present study support the relationships described in the FNMWCF model-specifically, that belonging fostered through culture is a significant predictor of engagement in land-based activities. This finding supports existing models that describe how increased engagement in cultural practices and identities among Indigenous communities is protective against adverse physical and mental health outcomes, including racial discrimination, colonialism, and historical trauma [33,38,39,49]. For example, cultural resilience has been significantly associated with mental, physical, emotional, and spiritual wellbeing, including self-reported physical health [49].…”
Section: Discussionsupporting
confidence: 82%
“…The benefit of culture as both a process one actively engages in and/or an outcome indicator has been conceptualized in a variety of ways within Indigenous health research. These include various processes and outcomes that relate to engagement in culture, including promoting cultural identity [35][36][37], cultural connectedness [38][39][40][41], cultural efficacy [42], and cultural continuity [43][44][45]. For example, among residential school survivors, connectedness to culture has been associated with better mental health outcomes [39].…”
Section: Cultural Approaches To Indigenous Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…Language plays an integral role in the lives of humans; the loss of language has profound human cost because it is through language that we encode and transmit cultural and intellectual knowledge (Evans, 2010; Holtgraves & Kashima, 2008; Vygotsky, 1962), or as Hale (1992) put it, ‘the priceless products of human mental industry’ (p. 36). Language also asserts our social identity as members of a particular culture or cultures (Gallois et al, 2005; Giles et al, 1991), and in minority groups its preservation is linked to higher wellbeing (Gibson et al, 2021; Hallett et al, 2007). Language loss also represents a significant loss for our science; in scientific terms, every language death represents a lost opportunity to understand the boundaries of diversity in the human language faculty.…”
mentioning
confidence: 99%
“…Scientific discourse on this topic is limited, but research has found engagement in cultural activities to be a protective factor. For example, it enhanced family functioning (Lohoar et al, 2014), it protected youth from suicide (Berry et al, 2010; Burgess et al, 2009; Gibson et al, 2021), and it was considered central to healthy child development in First Peoples from Western Australia (Scrine et al, 2020). Public schools that engaged children in learning traditional First Peoples languages found that this strengthened students’ development of cultural identity, pride, and self-worth, which increased their engagement in learning (Korff, 2019; Purdie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%